Chapter Introduction - Bartuschat, Johannes (Reti Medievali E-Book, 2020)
This volume aims to foster the dialogue between two usually distinct scholarly traditions: on the one hand, the studies revolving around cultural and political activity, as well as the didactic, theological, religious and pastoral initiatives undertaken by the Dominican Order in the urban context; on the other hand, the scholarship on the history of Florence between the thirteenth and fourteenth centuries, seen as a case study representative of the evolutions of late medieval communal institutions in the Italian peninsula. The essays focus on the reciprocal interactions and influences between religious and political cultures, along with those between mendicant and lay contexts.